Radiological Outcomes of Distal Radius Fractures Managed with 2.7mm Volar Locking Plate Fixation-A Retrospective Analysis - Kotian, Prem (J Clin Diagn Res, 2017)
INTRODUCTION: Distal radius fractures accounts for around 15% of all fractures diagnosed and treated in the emergency rooms. These fractures usually result secondary to high velocity injury such as a motor vehicle accident or fall on an out stretched hand. In the elderly, it is a common fragility fracture. Volar Locking Compression Plates (LCP) is effective devices for fixation of the distal radius fractures. There is a lacuna with regard to literature on the 2.7 mm volar LCP and the current study retrospectively assesses the postoperative radiological outcomes. AIM: To measure the radiological outcomes in patients with displaced distal radius fractures managed with 2.7 mm volar LCP fixation using Sarmiento’s Modification of Lindstorm Criteria. MATERIALS AND METHODS: A retrospective study was conducted in the Department of Orthopaedic Surgery at Kasturba Medical College Allied Hospitals, Mangalore from May 2014 to July 2016. All displaced distal radius fractures of skeletally mature patients who underwent volar locking plate fixation between May 2014 to July 2016 and follow up with X-rays at six weeks and three months were included as part of the study. The study comprised of 20 patients and fractures were classified using the AO and Melone’s classification systems. The radiological outcome was scored based on Sarmiento’s Modification of Lindstorm Criteria. RESULTS: Post operative check X-rays were analysed at immediate post operative, six weeks and three months. The mean immediate post operative radial shortening, decrease in radial deviation and loss of palmar tilt were 4.08±2.23, 5.91±4.01and 4.11±3.29 respectively. The corresponding values at last follow up were 4.71±2.31, 7.9±5.13 and 4.91±3.32 respectively. No statistically significant difference (p=0.930;874;716) in radial shortening, decrease in palmar angulation and loss of radial deviation was seen till the final follow up. Sarmiento’s Modification of Lindstorm Criteria showed a good radiological outcome in 60% followed by fair in 25% and excellent in 15%. CONCLUSION: Use of 2.7 mm volar LCP showed good to excellent post operative radiological outcomes in majority of the cases. The fracture reduction achieved in the immediate post operative period is maintained throughout the follow up duration.